A SYSTEMATIC REVIEW OF FACTORS AFFECTING NURSES’ PERFORMANCE IN HOSPITALS - Tasnidar; Syamsul Amar; Vidyarini Dwita (RADJA PUBLIKA, 2025)
A systematic review is therefore needed to consolidate existing evidence and identify the dominant factors influencing nurses’ performance in Indonesian hospitals. This study employed a systematic review approach by screening 15 national empirical journals published between 2020 and 2025. The inclusion criteria focused on studies discussing nurse performance in hospital settings, written in Indonesian or English, and employing quantitative or qualitative methods. Data were analyzed thematically, focusing on three main dimensions: individual, organizational, and external factors. The findings indicate that nurse performance in Indonesian hospitals is influenced by multiple interrelated dimensions. Individual factors include motivation, competence, emotional intelligence, and psychological well-being, which directly affect job outcomes. Organizational factors such as leadership style, workload distribution, supervision, reward systems, and work environment play a dominant role in shaping performance consistency and job satisfaction. Meanwhile, external or environmental factors including health policies, technological advancements, and societal expectations act as contextual determinants that either support or hinder performance improvement. The synthesis underscores the interdependence of personal, institutional, and systemic elements in achieving optimal nurse performance. Nurse performance in Indonesia is a multidimensional construct influenced by the synergy between individual capacity, organizational management, and external healthcare systems